2000
DOI: 10.1021/jp000101j
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of VX, GD, and HD with Nanosize CaO:  Autocatalytic Dehydrohalogenation of HD

Abstract: Room-temperature reactions of the chemical warfare agents VX, GD, and HD with nanosize CaO (AP-CaO), and HD with commercial CaO have been studied using solid-state MAS NMR. VX and GD hydrolyze to yield surface-bound complexes of nontoxic ethyl methylphosphonate and pinacolyl methylphosphonate, respectively. The kinetics are characterized by an initial fast reaction followed by a slower, diffusion-limited reaction. Similar behavior is observed for HD on either dried or hydrated AP-CaO and CaO. On partially hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
210
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 307 publications
(221 citation statements)
references
References 17 publications
6
210
0
1
Order By: Relevance
“…Results have demonstrated that with decrease in polarity along with increasing the time and temperature, the intensity of the AUC data of CEPS was declined respect to that of toluene, and higher amounts of this molecule were decontaminated, which are illustrated by new peaks at retention times of 9.6 and 12.5 min referring to the products, respectively. Finally, the experiments clearly noted that the perfect decontamination (100 %) occurred in n-hexane at 55°C after 1 h. It should be considered that the base sites exist on the surface of metal oxides, no matter, the surface is acidic, basic, or neutral [5]. Thus, these sites will not withstand in polar solutions, because the polarity of solution interferes with polar reactions between analyte and transition sites of adsorbent which both are polar.…”
Section: Gc Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…Results have demonstrated that with decrease in polarity along with increasing the time and temperature, the intensity of the AUC data of CEPS was declined respect to that of toluene, and higher amounts of this molecule were decontaminated, which are illustrated by new peaks at retention times of 9.6 and 12.5 min referring to the products, respectively. Finally, the experiments clearly noted that the perfect decontamination (100 %) occurred in n-hexane at 55°C after 1 h. It should be considered that the base sites exist on the surface of metal oxides, no matter, the surface is acidic, basic, or neutral [5]. Thus, these sites will not withstand in polar solutions, because the polarity of solution interferes with polar reactions between analyte and transition sites of adsorbent which both are polar.…”
Section: Gc Analysismentioning
confidence: 98%
“…Lately, reports have revealed that there is a great interest in use of solid sorbent decontaminants, such as nano metal oxides. Several nanocrystalline metal oxides, such as CaO [5], MgO [6][7][8], Al 2 O 3 [6][7][8][9], and ZnO [10], have been synthesized as adsorbents and catalysts using in various scientific fields. One of the most notable fields is their utilization for multiple defense applications, such as nuclear, biological, chemical (NBC) warfare, destructive adsorption, and decomposition of acid gases and polar organics, including CWAs and their mimics [11][12][13].…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…The activation energy was computed by temperature dependence conductivity curve. Ionic and electronic transference numbers (t ion and t ele ) were evaluated by means of Wagner's DC polarization technique, 18,19 degree of amorphosity by X-ray diffraction technique using a Philips PW 1710 diffractometer (using Cu-Kα radiation), surface morphology of the samples through SEM associated with EDS using JEOL JSM-5800 system. The thermal stability was studied by thermogravimetric analysis using TGA instruments (SDT 2960) and DSC (Perkin Elmer).…”
Section: Physical and Electrochemical Characterizationmentioning
confidence: 99%
“…Nerve agents GB (isopropyl methylphosphonofluoridate), GD (pinacolyl methylphosphonofluoridate), and VX [O-ethyl-S-(2-diisopropylamino)ethyl methylphosphonothioate] hydrolyze on metal oxides [1][2][3][4][5] and concrete, [6][7][8] forming their corresponding phosphonic acids (Scheme 1). Previous work examining these reactions on γ-Al 2 O 3 by 31 P and 27 Al MAS NMR 3 showed binding of these species to the alumina surface (surface-complexes 4 and 5; Scheme 3 below) the formation of discrete aluminophosphonate species (6 and 7; Scheme 3 below) via surface erosion and the secondary hydrolysis of VX-derived ethyl methylphosphonate (EMPA) to methylphosphonate (MPA).…”
Section: Introductionmentioning
confidence: 99%